Factors Associated with the Infrastructural Development of a Rural Market: Current Conditions and Future Priorities (American Journal of Innovation in Science and Engineering, 2024)
This paper tried to explore the current conditions of the physical infrastructure, including water, sanitation, waste management, drainage systems, environmental conditions, etc., of the Katihar bazaar. The study used a mixed-methods approach, while a semi-structural survey questionnaire and guidelines were used. A total of one hundred and twenty-eight respondents were surveyed, while six key KII and two FGD sessions were conducted. However, the study found that the Katihar market, one of northern Bangladesh’s oldest weekly markets, faces challenges such as poor drainage, narrow drains, and inadequate facilities for shopkeepers and customers. The market has a diverse population of middle-aged adults aged 47–80, with a small proportion of women. During the COVID-19 pandemic, the market was forced to open until midnight (12 p.m.), with 94% of shoppers wearing masks. Moreover, the market has one functional public toilet, no specialized facilities for women, transgender people, and PWDs, and insufficient water and hand washing facilities.